The Clinical Characteristics and Prognosis of AYA and Older Adult ETP-ALL/LBL: A Real-World Multicenter Study in China - Xiao, Jinyan; Cai, Zihong; Wang, Hao; Li, Xuekai; Zhou, Biqi; Liu, Yujie; Wang, Ying; Xu, Peipei; Wang, Li; Wu, Depei; Dou, Liping; Zhou, Hongsheng; et al. (Frontiers in Oncology, 2022)
Early T-cell precursor (ETP) lymphoblastic leukemia/lymphoma is a high-risk T lymphoblastic leukemia/lymphoma (T-ALL/LBL) subgroup. We performed a real-world multicenter study to explore the clinical characteristics and prognosis of adolescent and young adults (AYA) and older adult ETP leukemia/lymphoma. A total of 103 patients with ETP-ALL/LBL in five centers in China between January 2016 and February 2021 were included in this study. The median age was 29 years (range, 15–70 years). Next-generation sequencing was performed in 94 patients and revealed that NOTCH1 (35.1%, 33 cases) was the most frequently mutated gene, followed by JAK3 (16.0%, 15 cases), PHF6 (13.80%, 13 cases) and EZH2 (11.70%, 11 cases). Complete remission (CR) was obtained in 74.2% (72/97) of patients, and 6 relapsed/refractory patients received a decitabine combined with AAG priming regimen as reinduction therapy with a CR rate of 50%. With a median follow-up of 18 months (0.5–60 months), the 2-year overall survival (OS) and relapse-free survival (RFS) rates for the entire cohort were 54% and 57.7%, respectively. Allogeneic stem cell transplantation (allo-SCT) was performed in 59.8% (58/97) of patients. After landmark analysis at 6 months, the 2-year OS rates was 77% of patients with allo-SCT at CR1 and 25% of patients with chemotherapy alone (p < 0.001). A multivariate analysis suggested that allo-SCT and CR after the first course induction were independent prognostic factors for OS. Collectively, we reported the largest cohort study with AYA and older adult ETP-ALL/LBL, and we found that ETP-ALL/LBL was highly invasive and had a poor long-term prognosis. Allo-SCT could significantly improve ETP-ALL/LBL patient survival.